Analysis of Factors Influencing Academic Cheating in Online Learning - Risma Niswaty; Wahyuni Perdani Cindykiawan; Haedar Akib; Isgunandar Isgunandar (Jurnal Office, 2023)
Academic cheating is any dishonest act committed by students in order to gain achievement in the academic realm. independent variable (X) and academic fraud in online learning as the dependent variable (Y). This study analyzes the factors that encourage students to commit fraudulent behavior, especially in online learning. This study used observation data collection techniques, questionnaires and documentation by collecting sample data of 96 students. While the data analysis technique used is descriptive statistical analysis. The regression model feasibility test tool used is the classical assumption test. The hypothesis testing tools used are simple linear regression analysis, multiple linear regression analysis, T test, F test and R2 test. The results of this study prove that there is a positive and significant influence of each variable from pressure, opportunity, rationalization, ability and arrogance towards academic cheating in online learning partially and simultaneously.